Il buco, or Underground Language in the Anthropocene - Past, Elena (Aesthetica Preprint, 2023)
This article follows the search for a cinematic language adequate to address the vast temporal and spatial scales of the Anthropocene, by examining Il buco, a film directed by Michelangelo Frammartino (2021). The film reconstructs a 1961 expedition by the Italian Geological Expedition to explore the Bifurto cave in the Parco Nazionale del Pollino, Calabria, and I suggest that in the process, it launches a quest for an underground cinematic language for the Anthropocene: a language that must reckon with visual, spatial, and acoustic limits. Il buco, which opens with historic footage of the Pirelli Tower in Milan, architects a vertical landscape in which commercialized words above ground are counterbalanced by the audio-visual language of the underground. In the Bifurto abyss, human language abstracts and dissolves, the language of material prosperity falls flat, and cinema expresses its yearning to watch and to listen, even as cavernous darkness and resonance challenge its ability to do so.